2002
DOI: 10.1007/s00122-001-0849-1
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of Ty1-copia and Ty3-gypsy retroelements within the Triticeae EST databases

Abstract: The frequency of Ty1-copia-type and Ty3-gypsy-type retrotransposons in the International Triticeae EST Consortium (ITEC) database (61,942 sequences: 82% wheat, 10% barley, 8% rye) and the DuPont EST database (86,628 wheat sequences) was estimated using BLASTN searches. These ESTs were obtained from 94 cDNA libraries from different tissues (leaves, roots, spikes, flowers and seeds) and different growing conditions, excluding subtracted and normalized cDNA libraries. Triticeae EST databases were screened using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 18 publications
4
17
0
2
Order By: Relevance
“…Of the LTR retrotransposons, 38 are members (12), Latidu (2), Jeli (28), lfis (2), Hawi (2), Fatima (1), Erika (1), Laura (2)) and 7 are members of Ty1-copia family (Angel (3), Leojyg (2), WIS (1)), copia-like (1) and 2 are novel LTRs. The Ty3-gypsy and Ty1-copia elements are found in 0.35% (45 out of 17 949 ESTs) of endosperm ESTs, which is higher than what was reported earlier for sets of ESTs derived from other wheat cDNA libraries (Echenique et al 2002), including cDNA libraries constructed from tissues of plants subjected to stress. The Class II repetitive elements, which utilize a DNA-intermediate in a cut-and-paste transposition, are represented by CACTA (Wicker et al 2003) with 34 out of 112 ESTs similar to this repetitive element (30%).…”
Section: Genes Of Unknown Functionmentioning
confidence: 46%
See 1 more Smart Citation
“…Of the LTR retrotransposons, 38 are members (12), Latidu (2), Jeli (28), lfis (2), Hawi (2), Fatima (1), Erika (1), Laura (2)) and 7 are members of Ty1-copia family (Angel (3), Leojyg (2), WIS (1)), copia-like (1) and 2 are novel LTRs. The Ty3-gypsy and Ty1-copia elements are found in 0.35% (45 out of 17 949 ESTs) of endosperm ESTs, which is higher than what was reported earlier for sets of ESTs derived from other wheat cDNA libraries (Echenique et al 2002), including cDNA libraries constructed from tissues of plants subjected to stress. The Class II repetitive elements, which utilize a DNA-intermediate in a cut-and-paste transposition, are represented by CACTA (Wicker et al 2003) with 34 out of 112 ESTs similar to this repetitive element (30%).…”
Section: Genes Of Unknown Functionmentioning
confidence: 46%
“…Retrotransposons, transposable elements which move via an RNA transcript, have been shown to be present in wheat EST sequences (Echenique et al 2002;. To test whether any of the endosperm genes represent fragments of transposable elements that are abundant in the wheat genome , we compared the 17 949 EST sequences to the sequences of transposable elements reported in wheat.…”
Section: Genes Of Unknown Functionmentioning
confidence: 99%
“…Surprisingly, it was found that abundant retroelements are rarely expressed, whereas those with a low copy number are often transcribed based on the analysis of the maize EST database (Meyers et al 2001). Although a detailed examination of the transcriptional activities of wheat retrotransposons has not yet been reported, analysis of the Triticeae EST database revealed that sequences homologous to both Ty3-copia and Ty1-copia retrotransposons are differentially expressed in the cDNA libraries from different tissues or under various biotic and abiotic stresses (Echenique et al 2002).…”
Section: Retrotransposons Are Abundant In the Gli-2 Locimentioning
confidence: 98%
“…Using RT-PCR, transcription of Reme1 in leaves was observed under normal conditions. This is fairly unusual for a low-copy retrotransposon such as Reme1; transcription in unstressed somatic tissues is typical for the abundant elements of the grasses (Suoniemi et al 1996;Meyers et al 2001;Vicient et al 2001;Echenique et al 2002;Araujo et al 2005;Gomez et al 2006). Transcripts in leaves, however, are unlikely to contribute to genome expansion because leaves do not generally give rise to floral meristems and consequently gametes.…”
Section: Reme1 Transcriptional Activationmentioning
confidence: 94%